2018
DOI: 10.1093/ibd/izy055
|View full text |Cite
|
Sign up to set email alerts
|

Anal Fistulas in Severe Perineal Crohn’s Disease: Mri Assessment in the Determination of Long-Term Healing Rates

Abstract: Therapeutic strategies for perianal fistulizing CD require robust anatomical and healing evaluations. Combined strategies using biologics to improve both drainage and secondary closure of the fistula tracts merit further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…Importantly, anatomical features of the anal fistula, including anterior fistula and supralevator extension, had a negative impact on the outcome of perianal fistulizing CD. These data are in line with previous studies [20]. Some anatomical features of fistula can be modified by surgical drainage techniques and lowering of the tract.…”
Section: Discussionsupporting
confidence: 92%
“…Importantly, anatomical features of the anal fistula, including anterior fistula and supralevator extension, had a negative impact on the outcome of perianal fistulizing CD. These data are in line with previous studies [20]. Some anatomical features of fistula can be modified by surgical drainage techniques and lowering of the tract.…”
Section: Discussionsupporting
confidence: 92%
“…Randomized control trials have been carried out on the combined use of biologicals and surgical closure, but success rates have been difficult to assess because it has been difficult to determine the contribution of each procedure . In a recent study surgical closure of the tract was shown to improve healing rates better than treatment with biologicals or thiopurines . However, half of the patients with perianal fistulizing CD relapsed within 5 years of discontinuation of anti‐TNFα .…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, MRI assessment was performed at referral and at months 6, 12 and 24 which allowed assessment of the evolution of the fistula tract activity. It has been shown that MRI assessment of the fistula tract is necessary to optimize therapeutic management [30]. According to MRI, fistula tract healing was observed in 46.6% at 12 months and in 61.4% at 24 months.…”
Section: Discussionmentioning
confidence: 99%